Surrogate Entrepreneurship and Artificial Intelligence Driven Accounting: Shaping a Sustainable Future through Digital Start-ups - Sharma, Asha (American Journal of Business Science Philosophy, 2024)
This study examines the impact of innovative technology, artificial intelligence (AI) driven accounting, and surrogate entrepreneurship on fostering a sustainable future, with a focus on digital start-ups. Surrogate entrepreneurship refers to managing ventures on behalf of other entities rather than for personal ownership. Digital start-ups can harness advanced technologies like blockchain and AI to improve transparency, accuracy, and efficiency in accounting practices. Data were gathered through a structured questionnaire using a five-point Likert scale from 354 respondents, including entrepreneurs, accountants, business managers, and auditors in Southern Rajasthan. Partial least squares structural equation modeling (PLS-SEM) was utilized to analyze complex relationships between latent and observable variables. The results indicate that innovative technology, AI-driven accounting, and surrogate entrepreneurship significantly influence sustainable futures, accounting for 64.4% of the variance in digital start-ups’ contributions to sustainability. These findings provide valuable managerial insights into sustainable finance strategies and underscore the critical moderating roles of digital start-ups and surrogate entrepreneurship in driving sustainable development.